Design of advanced controllers for power system stability enhancement - Gao, Xuxing (2009)
Transient stability is an important property of power system control, improving the stability of a power system under small and large disturbances is one of the most important problems in power system control. Traditional PID controllers are widely used in power system control, to overcome the limitation of traditional PID controller, in this project, new controllers were designed based on single-machine infinite-bus system model to enhance transient stability and achieve better performances. Two advanced controllers namely DFL-LQ Optimal Controller and New PID reset had been designed and system performances were evaluated in simulation and compared with traditional PID controller. DFL-LQ Optimal Controller apples liner control theory to design a feedback control after direct feedback linearization. New PID Reset controller was to reset the integral part of the PID controller at a very short period. DFL-LQ Optimal Controller is a very robust controller to enhance transient stability. But the good performance of New PID Reset controller is not guaranteed, but it further improved by introducing more control vectors. The design methods applied in this project can be extend to multi-machine power system.